2013
DOI: 10.1002/micr.22169
|View full text |Cite
|
Sign up to set email alerts
|

Venous coupler size in autologous breast reconstruction—does it matter?

Abstract: Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…Broer et al have shown that a coupler size of less than or equal to 2.0 mm is more likely to result in venous insufficiency (6.7%) compared with the 2.5 mm (2.3%) and 3.0 mm (1.1%) sizes. 26 In this study, we did not observe venous insufficiency, especially with TMG flaps which required smaller coupler sizes. However, it is not possible to be completely certain that 100% of the venous anastomoses were patent because 15.2% of the flaps had double branching.…”
Section: Discussionmentioning
confidence: 46%
“…Broer et al have shown that a coupler size of less than or equal to 2.0 mm is more likely to result in venous insufficiency (6.7%) compared with the 2.5 mm (2.3%) and 3.0 mm (1.1%) sizes. 26 In this study, we did not observe venous insufficiency, especially with TMG flaps which required smaller coupler sizes. However, it is not possible to be completely certain that 100% of the venous anastomoses were patent because 15.2% of the flaps had double branching.…”
Section: Discussionmentioning
confidence: 46%
“…Some studies then proceeded to histopathology, computed tomography, or magnetic resonance imaging to confirm the diagnosis, often without a description of how fat necrosis is defined in these imaging modalities. 4,5,28,29 …”
Section: Resultsmentioning
confidence: 98%
“…Apart from the generally accepted risk factors such as smoking, diabetes, and obesity, some studies also identified associations between flap complications and flap characteristics (eg, perforator selection and number, number of veins and their size) or adjuvant treatment (eg, radiotherapy). 110 Despite missing consensus and insufficient evidence on the predictors of complications, data on potential risk factors are helpful for patient selection and preoperative planning.…”
mentioning
confidence: 99%